The mortgage interest deduction and its impact on homeownership decisions - Hilber, Christian A. L.; Turner, Tracy M. (My University, 2013)
This paper examines the impact of the combined U.S. state and federal mortgage interest deduction (MID) on homeownership attainment, using data from 1984 to 2007 and exploiting variation in the subsidy arising from changes in the MID within and across states over time. We test whether capitalization of the MID into house prices offsets the positive effect on homeownership. We find that the MID boosts homeownership attainment only of higher-income households in less tightly regulated housing markets. In more restrictive places, an adverse effect exists. The MID is an ineffective policy to promote homeownership and improve social welfare.
Keywords: Mortgage interest deduction (MID); Homeownership attainment; United States; Tax expenditures; Local housing markets; Income status